1988
DOI: 10.1016/0003-2697(88)90031-0
|View full text |Cite
|
Sign up to set email alerts
|

Solid phase enzyme-linked competitive binding assay for riboflavin

Abstract: A new solid-phase enzyme-linked assay for riboflavin (vitamin B2) is described. The assay is based on the competition between analyte vitamin molecules and a glucose-6-phosphate dehydrogenase-3-carboxymethylriboflavin conjugate for a limited number of riboflavin-binding protein sites immobilized on Sepharose particles. Significant improvements in conjugate catalytic activity and thus detectability are achieved by optimizing the reaction conditions used to covalently link 3-carboxymethylriboflavin to the enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…However, the rate of binding is significantly slowed after the first 2 h and thus, in subsequent competitive binding assays, we chose a 2.5 h time period for all incubations between the conjugate, immobilized binder, and standards or samples. Interestingly, in related work [5], we observed that the overall kinetics of conjugate binding are enhanced when the solidphase has lower levels of protein coverage. Therefore, in the present effort, we purposely prepared our solid-phase reagent using high mass ratios of Sepharose beads to R-protein.…”
Section: Resultsmentioning
confidence: 61%
“…However, the rate of binding is significantly slowed after the first 2 h and thus, in subsequent competitive binding assays, we chose a 2.5 h time period for all incubations between the conjugate, immobilized binder, and standards or samples. Interestingly, in related work [5], we observed that the overall kinetics of conjugate binding are enhanced when the solidphase has lower levels of protein coverage. Therefore, in the present effort, we purposely prepared our solid-phase reagent using high mass ratios of Sepharose beads to R-protein.…”
Section: Resultsmentioning
confidence: 61%
“…Any remaining DMF, DCC, or sulfo-NHS was removed by ethanol, a solvent in which the activated ester product is not soluble. The activated ester (powder form) prepared in this manner was stable for at least 6 months when stored below 0 °C …”
Section: Methodsmentioning
confidence: 99%
“…Efforts to develop high-affinity antibodies selective for riboflavin have met with limited success (Monroe, 1984), although recently Wang et al (2013) have claimed development of a sensitive and specific polyclonal antibody for riboflavin. Natural binders are utilized in most assays, such as riboflavin-binding protein from chicken egg white (Fazekas, Menendez, & Rivlin, 1974;Bashor & Tillotson, 1978;Geun & Meyerhoff, 1988).…”
Section: Immunoassaysmentioning
confidence: 99%